Application of advanced exergy analysis for optimizing the design of carbon dioxide pressurization system. (1st August 2021) - Muhammad, Hafiz Ali; Lee, Beomjoon; Cho, Junhyun; Rehman, Zabdur; Choi, Bongsu; Cho, Jongjae; Roh, Chulwoo; Lee, Gilbong; Imran, Muhammad; Baik, Young-Jin
Abstract: The pressurization of carbon dioxide is an integral step of the carbon capture and storage process; a key technology frontier for the decarbonization of power and heat industry. Effective measures to improve the pressurization scheme directly translate into the reduction of process costs. This study aimed to reduce the energy expenditure of the carbon dioxide pressurization process by assisting the conventional carbon dioxide multi-stage compressors with an Ammonia (R717) or Propane (R290) based heat-pump system. In these systems, carbon dioxide is liquefied in the heat-pump after being compressed to an intermediate liquefaction pressure. The liquefied carbon dioxide is subsequently pumped to the target pressure. In this study, the advanced exergy analysis, in addition to the conventional energy analysis is applied to design and optimize the carbon dioxide liquefaction system using a heat pump. The initial conventional exergy analysis reveals that 43.76% of total fuel exergy is destroyed and lost. Subsequently, the advanced exergy analysis is performed to pinpoint the source of total irreversibility (exergy destruction), calculate the avoidable exergy destruction in the system and figure out potential measures to improve the system's performance. The advanced exergy analysis reveals the avoidable exergy destruction is 48.85% and 51.20% of the total exergy destruction for R290 and R717, respectively. Furthermore, the avoidable exogenous exergy destruction is 16% and 19%, respectively. The results also show that for R717, the extent of improvement is in the following order, Condenser > Compressor > Evaporator > Expansion valve. With this information, a systematic approach is devised and followed to optimize the operating parameters and design of the heat-pump system. Furthermore, in the proposed system, 2328.6 kW of exergy is lost to the environment. To recover this exergy loss, the heat pump-assisted pressurization scheme is integrated with a supercritical carbon dioxide power cycle which generated 1191.00 kW of electric power. The results reveal that the electrical power consumed by the proposed system optimized through advanced exergy analysis is 15.5% lower than that consumed by a benchmark system. The study demonstrates the effectiveness of advanced exergy analysis and the approach presented here can be extended to other energy conversion systems to maximize the energy and exergy savings for sustainable development. Graphical abstract: Image 1 Highlights: An advanced exergy analysis of a CO2 pressurization strategy is carried out. Ammonia refrigeration system shows 19% of avoidable exogenous exergy destruction. 15.5% electric power saving is achieved by minimizing avoidable exergy destruction.